The Role of Foliar Nutrition in Tolerance of Wheat (Triticum aestivum L.) Varieties under Drought Stress - Sleibi, Azhar Taher; Abdullah , Asaad Kadhim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Drought stress resulting from the depletion of available water in the soil leads to disturbances in the plant’s metabolic processes, reducing productivity due to its decreased ability to absorb water and essential nutrients. This study aimed to evaluate the interactive effects of three bread wheat varieties (Adna 99, Bohooth 22, and Wafia), three drought stress levels (25% control, 50%, and 75% depletion of available water), and foliar application of micronutrients(control) iron (Fe), zinc (Zn), copper (Cu), and manganese (mn) at 100 mg L-¹) and no spraying on agro-biochemical characteristics. The experiment was conducted using a randomized complete block design (RCBD) with three replications. The results showed that as drought conditions got worse, from 25% to 75%, the antioxidant activity increased a lot, with superoxide dismutase (SOD) going up by 138.44%, catalase (CAT) by 81.40%, α-tocopherol by 9.88%, and glycine betaine by 11.55%. On the other hand, important factors for crop yield went down during severe drought, with the number of spikes dropping by 23%, grain yield by 20.77%, weight of a thousand grains by 9.25%, biological yield by 11.53%, and harvest index by 16.33%. Among the genotypes tested, Adna 99 performed the best under severe drought when foliar micronutrients were applied, followed by Bohooth 22, while Wafia was very sensitive to both drought and lack of micronutrients. These results suggest that using foliar micronutrients along with drought-resistant genotypes could be an effective way to improve wheat production when water is scarce. Future research should focus on the molecular validation of antioxidant-related gene expression involved in drought tolerance mechanisms.